2007
DOI: 10.1161/circulationaha.106.624296
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Chronic Chagas Heart Disease

Abstract: Background-Chagas disease remains a significant public health issue and a major cause of morbidity and mortality in Latin America. Despite nearly 1 century of research, the pathogenesis of chronic Chagas cardiomyopathy is incompletely understood, the most intriguing challenge of which is the complex host-parasite interaction. Methods and Results-A systematic review of the literature found in MEDLINE, EMBASE, BIREME, LILACS, and SCIELO was performed to search for relevant references on pathogenesis and pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
640
1
94

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 718 publications
(770 citation statements)
references
References 126 publications
10
640
1
94
Order By: Relevance
“…However, more recent studies using more sensitive methodologies have shown clear correlations between the presence of the parasite and the inflammatory processes that underlie the pathological processes associated with chronic Chagas disease (Tarleton et al 1997, Tarleton & Zhang 1999, Tarleton 2001, Marin-Neto et al 2007). This fact, coupled with the finding that T. cruzi-specific CD8+ and CD4+ T cells, are consistently associated with inflammatory infiltrates rich in Th1 cytokines, has led to the notion that parasite persistence is a necessary and sufficient condition to generate and sustain a Th1-biased inflammatory response in infected tissues, which may include autoimmune phenomena (Tarleton et al 1997, Tarleton & Zhang 1999, Tarleton 2001, Marin-Neto et al 2007.…”
Section: Relevance Of Specific Chemotherapy For Chagas Disease and LImentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent studies using more sensitive methodologies have shown clear correlations between the presence of the parasite and the inflammatory processes that underlie the pathological processes associated with chronic Chagas disease (Tarleton et al 1997, Tarleton & Zhang 1999, Tarleton 2001, Marin-Neto et al 2007). This fact, coupled with the finding that T. cruzi-specific CD8+ and CD4+ T cells, are consistently associated with inflammatory infiltrates rich in Th1 cytokines, has led to the notion that parasite persistence is a necessary and sufficient condition to generate and sustain a Th1-biased inflammatory response in infected tissues, which may include autoimmune phenomena (Tarleton et al 1997, Tarleton & Zhang 1999, Tarleton 2001, Marin-Neto et al 2007.…”
Section: Relevance Of Specific Chemotherapy For Chagas Disease and LImentioning
confidence: 99%
“…This fact, coupled with the finding that T. cruzi-specific CD8+ and CD4+ T cells, are consistently associated with inflammatory infiltrates rich in Th1 cytokines, has led to the notion that parasite persistence is a necessary and sufficient condition to generate and sustain a Th1-biased inflammatory response in infected tissues, which may include autoimmune phenomena (Tarleton et al 1997, Tarleton & Zhang 1999, Tarleton 2001, Marin-Neto et al 2007.…”
Section: Relevance Of Specific Chemotherapy For Chagas Disease and LImentioning
confidence: 99%
“…It has been estimated that approximately 30% of infected persons evolve toward the chronic phase, which may include pathological involvement/damage to the heart, esophagus and/or colon [11]. Cardiac damage is the most severe and frequent outcome [10].…”
Section: Introductionmentioning
confidence: 99%
“…Las principales formas de transmisión de la enfermedad de Chagas son vectorial, transfusional y congénita, así como otras (oral, trasplantes, accidentes en laboratorios) (6,7). La vía más importante de transmisión y mantenimiento de la endemia chagásica se asocia con la pobreza y ocurre en viviendas con condiciones precarias, tanto en áreas rurales como en periurbanas, en las cuales abundan las colonias de triatominos asociadas con reservorios domésticos y peridomésticos que sirven como fuente de alimentación (8).…”
Section: Discussionunclassified